A Mini Review on Low Carbon Steel in Rapid Cooling Process - Sazali, Norazlianie; Abdullah, Siti Noradila (Journal of Advanced Research in Applied Mechanics, 2020)
One of the latest technologies used in sheet metal production is hot stamping. It is a combination of forming and rapid cooling to create stronger components of sheet metal products. To handle a wide range of sheet metal that is suitable for hot forming, this short review emphasizes the study on microstructure changes during rapid cooling on different sheet metal thickness of low carbon steel. The mechanical properties like hardness, toughness and ductility can be altered by intense heat treating on steel and rapid cooling it to produce different mechanical properties. To change the characteristics of steels is by heat treating whereby altering the diffusion and cooling rate within its microstructure by changing the grain size at different phases and changing the molecular arrangement. The mechanical properties of the low carbon steel with different thickness may be different due to the microstructure behaviour after heat treating. Finally, the behaviour of the microstructure of low carbon steel changes with different thickness that is affecting the mechanical properties after heat treating and quenching process.